ID: 45. Issue 1 (November 2015) - Schmeisser, Hana; Balinsky, Corey; Singh, Kavita; Sreedhara, Karthik; Dolan, Michael; Garboczi, David; Zoon, Kathryn
<x xml:space="preserve">Abstract</x> IFIT3, alternatively known as Retinoic Acid Induced Gene G (RIG-G) or IFI60, is a member of the ISG56/IFIT1 gene family together with IFIT1, IFIT2, and IFIT5. All these gene products are defined by a single repeated structural motif, the tetratricopeptide repeat, which contains 34 amino acids and adopts a basic helix-turn-helix fold. Members of the ISG56/IFIT1 gene family have been found to play roles in inhibition of translation and protein synthesis through interaction with eukaryotic initiation factor (eIF3), inhibition of interferon beta production, inhibition of cell migration, and promotion of antiproliferative and antiviral effects. The IFIT3 protein is composed of 490 amino acids, has an apparent MW of 58 kDa, and has been shown in our previous study to be highly inducible by interferon alpha, thus implicating an important role for IFIT3 in interferon-mediated antiviral action (Schmeisser et al., 2010). To further characterize the role of IFIT3 in the antiviral response, we studied the effect of its overexpression on virus titers of VSV (Vesicular Stomatitis Virus), and EMCV (Encephalomyocarditis Virus), protein synthesis, and interaction with IFIT1. Although the precise mechanism is still unknown, IFIT3 demonstrated a clear antiviral effect against both viruses. Moreover, IFIT3 interacts with IFIT1, and this interaction may play a role in regulation of protein synthesis.